PENGARUH TINGKAT PENDIDIKAN TERHADAP KINERJA KARYAWAN PADA PT.ASTRA CREDIT COMPANIES (ACC) KOTA JAMBI - Padli, Husni; Andriani, Lili (Universitas Batanghari Jambi, 2022)
This study aims to determine (1) there is no significant effect between the level of education on employee performance at PT. Astra Credit Companies (ACC) Kota Jambi. (2) There is a significant influence between the level of education on the performance of employees at PT. Astra Credit Companies (ACC) Kota Jambi. This type of research is using a quantitative descriptive research approach. The number in this study is 100 employees and as a research sample 48 employees. The technique of collecting data in this study is by distributing questionnaires to research respondents. 1. Education level There is no significant effect between education level on employee performance at PT. Astra Credit Companies (ACC) Kota Jambi. 2. Employee performance There is a significant influence between the level of education on employee performance at PT. Astra Credit Companies (ACC) Kota Jambi. Keywords; Education Level, Employee Performance.